Endurance development in Taekwondo according to the Tabata protocol - Mischenko, N.; Kolokoltsev, M.; Gryaznykh, A.; Vorozheikin, A.; Romanova, E.; Suslina, I. (Journal of Physical Education and Sport, 2021)
he scientific literature presents a limited number of studies on Tabata training use for endurance, as the main physical quality for taekwondo athletes, development. he purpose of the research: to prove experimentally Tabata protocol training effectiveness to increase WTF taekwondo athletes' endurance. Research material and methods. The experiment was conducted at a sports school in Chelyabinsk (Russia). The study participants were 2 groups of athletes aged 16-18. All young men were engaged in taekwondo WTF at the stage of improving sports skills according to the program of the Russian federal standard of sports training in the sport «taekwondo ITF» (International Taekwondo Federation) (2019). In the main part of the training session, the experimental group conducted high-intensity interval training according to Tabata protocol (20-25 minutes) using a complex of strength, plyometric and coordination exercises with and without sports equipment. For a comparative analysis of the training process effectiveness in the control and experimental groups, the methods of anthropometry and physiometry, physical qualities and physical performance testing were used. Results. At the end of the experiment, all indicators improved in both observation groups. The increase in these indicators' values was higher in the boys of the experimental group: aerobic and anaerobic physical performance, absolute and relative hands muscles strength significantly increased. The indicators values of general, strength and speed endurance were higher than in the control group. Conclusions. High-intensity interval training according to Tabata protocol proved to be effective for general and special (strength and speed) endurance development in WTF taekwondo athletes at the stage of improving sports skills.